NANOBODY SYNTHESIS TO TARGET EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) IN COLORECTAL CANCER CELLS - Fatima Malik; Sara Hussain; Seo Jiwon (Yayasan Adra Karima Hubbi, 2025)
Colorectal cancer (CRC) is a leading cause of cancer-related deaths, with the overexpression of epidermal growth factor receptor (EGFR) playing a critical role in its progression. Current therapies face challenges in targeting EGFR effectively. To synthesize and evaluate nanobodies targeting EGFR in colorectal cancer cells, aiming to improve therapeutic specificity and efficacy. Nanobodies were synthesized using phage display technology and screened for high affinity to EGFR. In vitro studies involved colorectal cancer cell lines (HT-29, SW480, HCT116) to assess binding specificity, internalization, and cytotoxicity. In vivo studies used mouse models implanted with human colorectal tumors to evaluate biodistribution, tumor targeting, and therapeutic outcomes. Synthesized nanobodies demonstrated high binding affinity (KD in nanomolar range) and specificity to EGFR, inhibiting cancer cell proliferation by up to 70% and reducing tumor volume by 65% in mouse models. Stability tests confirmed nanobody resilience under various biological conditions. The study highlights the potential of nanobodies targeting EGFR as an effective therapeutic approach for colorectal cancer, with significant improvements in targeting specificity and tumor reduction. Further clinical trials are necessary to confirm these findings.